Trends in subjective income poverty rates in the European Union - Tomáš Želinský; Martina Mysíková; Thesia I. Garner (Global Labor Organization (GLO), 2021)
When developing anti-poverty policies, policy makers need accurate data on the prevalence of poverty. In this paper, we focus on subjective poverty, a concept which has been largely neglected in literature, yet remains a conceptually appealing way to define poverty. The primary goal of this study is to re-examine the concept of subjective poverty measurement and to estimate trends in subjective poverty rates in the European Union. Our estimations are based on a minimum income question using data from a representative survey, EU-SILC, and we find a decreasing trend in subjective poverty in 16 of 28 countries. Conversely, the official relative income poverty indicator exhibits increasing trends in eleven countries, with decreasing trends in only four countries. We believe that these trends may reflect changes in societies which have not been previously captured, and our results thus enrich the existing data on general poverty trends in the EU.
Keywords: I31; I32; 330; Subjective poverty; Minimum Income Question; intersection approach; EU-SILC; European Union